2020
DOI: 10.1111/and.13573
|View full text |Cite
|
Sign up to set email alerts
|

The heart rate recovery is impaired in participants with premature ejaculation

Abstract: Premature ejaculation (PE) is one of the most common sexual disorders in men. Excessive activity of the sympathetic nervous system is considered as one of the pathological mechanisms of PE. Heart rate recovery (HRR) is a noninvasive and easily applicable method for evaluating autonomic functions. We aimed to investigate the relationship between PE and HRR. This cross‐sectional study included 42 consecutive patients with lifelong PE and 98 healthy volunteers. All participants underwent stress tests according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Firstly, decreased erectile functioning could be a motivator to seek excitation transfer: One needs stronger stimuli to achieve sexual arousal or gratification (Smid & Wever, 2019). Also, higher sympathetic arousal has been related to smaller erections (Harte, 2013), less orgasms through normal intercourse (Costa & Brody, 2012), and more problematic erectile functioning (Rowland, 2010;Turan & Gürel, 2020). Therefore, we hypothesized that excitation transfer would be associated with decreased erectile functioning and increased resting state sympathetic arousal.…”
Section: The Current Studymentioning
confidence: 99%
“…Firstly, decreased erectile functioning could be a motivator to seek excitation transfer: One needs stronger stimuli to achieve sexual arousal or gratification (Smid & Wever, 2019). Also, higher sympathetic arousal has been related to smaller erections (Harte, 2013), less orgasms through normal intercourse (Costa & Brody, 2012), and more problematic erectile functioning (Rowland, 2010;Turan & Gürel, 2020). Therefore, we hypothesized that excitation transfer would be associated with decreased erectile functioning and increased resting state sympathetic arousal.…”
Section: The Current Studymentioning
confidence: 99%
“…In the ejaculation phase, the sympathetic nervous system facilitates the emission of seminal uid [15]. There are a few preliminary studies suggesting a role for sympathovagal imbalance in PE, with men with PE displaying higher levels of sympathetic activation than sexually functional controls in both non-aroused [16,17] and aroused [18] settings. In the case of autonomic imbalance, sympathetic overactivity might inhibit erection and facilitate ejaculation.…”
Section: Pe and Edmentioning
confidence: 99%
“…There are ve categories of ED based on IIEF-5 scores: Severe (5-7), moderate (8-11), mild to moderate (12)(13)(14)(15)(16), mild (17)(18)(19)(20)(21), and no ED (22)(23)(24)(25) [67].…”
Section: Penile Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Moreover, heart rate recovery after intense exercise has been found to be slower in men diagnosed with premature ejaculation than in controls, again suggesting an overactive sympathetic system. 25 Finally, a study of the sympathetic skin response on the penis showed that it was enhanced in men suffering from premature ejaculation. 26 All these observations coincide with data from male rats.…”
Section: Introductionmentioning
confidence: 99%